Plan de reforestación con especies nativas en la microcuenca alta del río Carrizal en la comunidad de Severino - Moreira Zambrano, María Roberta (2015)
The research aimed to design a reforestation plan for the conservation of native species in the community of Severino, in the high watershed of the river Carrizal, Quiroga Parish, Canton Bolivar, Manabi province, 173masl, at the geographic coordinates 17M0607098, 9895204UTM. it was run as a non-experimental research, the methods used were bibliographical, descriptive, observational techniques, surveys, interviews, interactive workshops and field visits. The results showed that people in the community selected three native tree species of choice as Laurel (Cordiaalliodora sp.) Cedro (Cedar pinacea) Fernan Sanchez Triplariscumingiana sp) for its ecological value and use value. It was determined that the level of training is poor, with 83% did not received any training on reforestation; 54% know what a native forest species is; 97% are interested in participating in a reforestation plan and 90% in its implementation; 72% prefer the morning, 73% know the native forest species; and 100% of them identified in the field. A reforestation plan based on community needs identified for reforestation of the affected areas. Reforestation plan of native specieswas socialized and at first start setting up the training program in reforestation, to recognize the type of soil and the needs of the same, according to the requirements and resources.